2007
DOI: 10.1007/s00418-007-0295-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro liberation of charged gold atoms: autometallographic tracing of gold ions released by macrophages grown on metallic gold surfaces

Abstract: The present study demonstrates that cultured macrophages are able to liberate gold ions from metallic gold surfaces, a process suggested to be called "dissolucytosis", in a way analogous to the release taking place when metallic implants are placed in a body. Using the ultra-sensitive autometallographic (AMG) technique, we demonstrate that murine macrophages grown on a surface of metallic gold liberate gold ions. Ultra-structural AMG reveals that the gold ions are located in an ultra-thin membrane-like structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 28 publications
1
50
0
1
Order By: Relevance
“…7,14,25 In vivo and in vitro studies have shown that metallic gold implants release gold ions in tissues and cell cultures as a result of interaction with oxidative agents most likely provided by macrophages. 4,18 Some believe that the pro-inflammatory properties of gold can be attributed to ionized gold and its metabolites. 4,5 The purpose of the present article is to investigate the tissue inflammatory response surrounding metallic gold beads implanted into dogs as a treatment for spontaneous osteoarthritis.…”
mentioning
confidence: 99%
“…7,14,25 In vivo and in vitro studies have shown that metallic gold implants release gold ions in tissues and cell cultures as a result of interaction with oxidative agents most likely provided by macrophages. 4,18 Some believe that the pro-inflammatory properties of gold can be attributed to ionized gold and its metabolites. 4,5 The purpose of the present article is to investigate the tissue inflammatory response surrounding metallic gold beads implanted into dogs as a treatment for spontaneous osteoarthritis.…”
mentioning
confidence: 99%
“…As opposed to Sethi et al (2002), using both wrought and as-cast CoCrMo, we observed that only as-cast CoCrMo suppressed IL-6 compared to TiAlV, but the increase in TNF-α was seen for both wrought and as-cast CoCrMo alloys. TNF-α increases osteoclast survival rate (Lee et al, 2001), transforms osteoclast precursors to mature osteoclasts (Lam et al, 2000), and activates resident nonactivated osteoclasts even at very low levels (e.g. 100 pg/ ml) (Fuller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These ligand-interactions and several others are the primarily interaction between implant surface and macrophages (Ziats et al, 1988) resulting in cytokine release independently of internalization of wear particles (Bi et al, 2002;Fritz et al, 2006;Nakashima et al, 1999). The release of metal ions take place as a result of the dissolucytes (macrophages) controlling the chemical milieu in the membrane (Danscher, 2002;Larsen et al, 2007) in a process called dissolucytosis. Co 2+ and Cr 3+ ions induce necrosis and apoptosis as well as secretion of TNF-α, IL-6, and PGE2 in various cell-types (Catelas et al, 2003;Lee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is recognized that gold ions inXuence the number and function of macrophages. Larsen et al (2007) now demonstrate that cultured macrophages are able to liberate gold ions from metallic gold surfaces in a way analogous to the release taking place when metallic implants are placed in a body. Using the ultra-sensitive autometallographic (AMG) technique, they show that murine macrophages grown on a surface of metallic gold liberate gold ions.…”
Section: Immune System and Adipocytesmentioning
confidence: 99%